Sobre el léxico de origen egipcio en las lenguas eslavas, en español y en otras varias lenguas (y II) - Alvarado, Salustio (Eslavística Complutense, 2007)
The Egyptian language is among the most ancient of mankind’s culture languages. Its reputation left an indelible mark on the languages within its cultural environement, especially Hebrew and Greek. It was through these languages that words of Egyptian origin, favoured by the condition of their specificity, reached every language in Europe, Slavonic languages being no exception